Новые виды листоверток (Lepidoptera, Tortricidae) из высокогорий Палеоарктики - Костюк, Ю.А. (Вестник зоологии, 1975)
The article deals with a description of three new species of leaf-rollers: Aphelia caucasica Kostjuk from the Great Caucasus (the Mamisonian pass), Pelochrista danilevskyi Kostjuk and Eucosma muguraxana Kostjuk from Tuva and North- Western Mongolia. Genitals of the only (with an intact abdomen) cotype of Pelochrista ruschana Obr. are depicted.